Prosedur Kerjasama Regional Dalam Pembangunan dan Pengelolaan Infrastruktur - Windyanti, Reny (Journal of Regional and City Planning, 2000)
The Law No. 22/1999 concerning Local Government has become a debate concerning whether or not local or the central government is ready to implement the law. Decentralization gives the opportunity for local governments to enchance their potential resources development. They can create competitiveness In city and regional development that in the end will improve the prosperity of the community. Sometimes, however, local governments have their own interest on development, that do not consider the impact to other regions and this cause a lot of conflict among regions. Hence the cooperation among authorities is needed in order to have an integrated development. One example of important aspect in development that needs an integrated approach is infrastructure. The availability of infrastructure will be highly demanded for the development — especially in the urban areas. Yet, for the recent time the infrastructure services cannot support the demand Hence, the regional approach will be a crucial option where local government develops a regional cooperation with other au theorities in infrastructure development and management. This paper tries to review how the procedure or regional cooperation is developed in the infrastructure development and management, particularly for regional solid waste disposal site.